Penerapan Klinikal Pathway Rosier pada Pasien Stroke Akut - Alde Afinturi Ajye; Al Afik; Cipto Wahyuning Utama (Sci-tech Journal, 2025)
Acute stroke is a condition in which a patient experiences a disorder in the blood vessels of the brain that disrupts the flow of blood to the brain, and the disorder can be in the form of blockage or rupture of blood vessels. Stroke can occur due to several diseases, such as hypertension and unhealthy lifestyles. The tool to establish a stroke diagnosis is ROSIER, or Recognition of Stroke in the Emergency Room, which provides several elements, including clinical symptoms, namely loss of consciousness, seizure activity, asymmetrical face, weakness in the hands, weakness in the legs, experiencing speech disorders, and decreased vision. Method: This study is a case study of patients with acute stroke who came to the ER, patients were assessed using the ROSIER clinical pathway after triage with 7 ROSIER elements when the total score is >0 then the possibility of having a stroke is high but if ≤0 then the possibility of having a stroke is slight. Results: The patient's total score is +2, which means that the patient has had a stroke and is supported by supporting examinations, namely a CT scan of the head, which shows intracerebral hemorrhage. Conclusion: Enforcement using a stroke diagnosis has proven to be effective and fast, so that it can be applied in the ER